2022
DOI: 10.2147/ppa.s351001
|View full text |Cite
|
Sign up to set email alerts
|

Primary Non-Adherence to Preventive Drugs and Associations with Beliefs About Medicines in Stroke Survivors

Abstract: Background: Medication non-adherence is a common problem in clinical practice. Little is known about stroke survivors' primary non-adherence to preventive drugs, and we hypothesised that their beliefs about medicines are associated with primary non-adherence. The objective was to describe primary non-adherence among stroke survivors and to assess associations between primary nonadherence to preventive drugs and beliefs about medicines. Methods: Questionnaires were sent to 797 individuals 3 months after stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition, poor LLT adherence can sometimes be unintentional and a consequence of forgetfulness or a lack of understanding of medication instructions. A cross‐sectional questionnaire study of stroke survivors showed no association between nonadherence to preventive drugs and personal beliefs about medicine and suggested that nonadherence might be associated with difficulties with memory and the need of help from next of kin 13 …”
Section: Challenges For Adherence To Currently Available Lltsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, poor LLT adherence can sometimes be unintentional and a consequence of forgetfulness or a lack of understanding of medication instructions. A cross‐sectional questionnaire study of stroke survivors showed no association between nonadherence to preventive drugs and personal beliefs about medicine and suggested that nonadherence might be associated with difficulties with memory and the need of help from next of kin 13 …”
Section: Challenges For Adherence To Currently Available Lltsmentioning
confidence: 99%
“…A cross-sectional questionnaire study of stroke survivors showed no association between nonadherence to preventive drugs and personal beliefs about medicine and suggested that nonadherence might be associated with difficulties with memory and the need of help from next of kin. 13 2.2 | Therapy-related factors…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to a stroke-preventive medication has been reported to be a promising way to prevent stroke recurrence. 11 However, medication adherence rates in stroke patients are poor. Multiple studies have reported that between 40% to 50% of stroke patients do not adhere to their medication.…”
Section: Introductionmentioning
confidence: 99%
“…4 Another study found that primary non-adherence, defined as failure to fill one or more new prescriptions within one month of hospital discharge, has been found associated with having difficulties with memory. 5 Also, individuals with chronic diseases often show high rates of medication non-adherence. [6][7][8] Negative beliefs about medications have been shown more common among non-adherent individuals, and these individuals also considered their drug treatment as less useful.…”
Section: Introductionmentioning
confidence: 99%